(untitled) (OCEM Journal of Management, Technology & Social Sciences, 2026)
This study explores the factors influencing stock market participation among youth in Bagmati Province, Nepal, with an emphasis on financial literacy, social influence, economic goals, FinTech accessibility, and risk perception. Utilising a quantitative design with a structured questionnaire distributed to one hundred fifty-seven (N = 157) young investors selected through convenience sampling, the research employed descriptive statistics, Spearman’s rank-order correlation, and multiple regression analysis via IBM SPSS and Microsoft Excel. Results indicate the regression model accounts for 94% of the variance in stock market participation (R² = 0.940), showcasing strong explanatory power. Financial literacy and knowledge were identified as the sole statistically significant predictor of stock market participation (β = 0.964, p < 0.001), confirmed by a high positive correlation (ρ = 0.975, p < 0.001). While economic and financial goals, FinTech accessibility, and risk perception showed positive bivariate relationships, their multivariate effects were not statistically significant, suggesting that financial literacy mediates these relationships. Conversely, social influence and herding behavior did not significantly impact participation. The findings indicate that informed investment decisions are predominantly influenced by financial knowledge, rather than peer influence or technological factors. This research highlights financial literacy as a crucial factor in youth engagement within Nepal’s capital market, emphasising its mediating role among various behavioral and economic influences on investment participation. The study offers important implications for policymakers, financial educators, regulators, and institutions focused on enhancing youth engagement through targeted financial education and investment awareness initiatives. Future research is encouraged to validate the proposed mediation framework with larger, more representative samples.